Knowledge, Motivation, and Environmental Awareness as Predictors of Vocational Students’ Recycling Attitudes - Hamidah Suryani; Fitry Purnamasari (International Journal of Pedagogy and Teacher Education, 2026)
Effective waste management remains a global challenge, particularly within educational institutions where practice-based and creative learning activities often generate considerable waste. Vocational programs such as Fashion Design and Culinary Arts produce residual materials that can potentially be reused through recycling, making students’ recycling attitudes an important concern for sustainability-oriented education. This study examined the influence of perceived knowledge, motivation, and environmental awareness on vocational students’ recycling attitudes in the Craft course. A quantitative cross-sectional survey design was employed involving 100 second-semester students from the Department of Family Welfare Education, Universitas Negeri Makassar. Data were collected using a validated and reliable questionnaire and analyzed using multiple linear regression with EViews 13. Classical assumption tests indicated that the dataset met the requirements of normality, absence of multicollinearity, and homoscedasticity. The findings showed that perceived knowledge, motivation, and environmental awareness were positive and significant predictors of students’ recycling attitudes, with motivation emerging as the strongest predictor. The regression model explained 83.57% of the variance in recycling attitudes. These findings suggest that recycling attitudes in vocational higher education are shaped not only by students’ knowledge, but also by motivational and awareness-related factors. The study provides practical insights for designing recycling-based projects and environmental literacy initiatives in vocational learning contexts.